À titre provisoire - made in France index, 60/100 - Delaborde, Jonas 1981-; Lejemmetel, Anna; Hegray, Hendrik 1981-; Hotu; Kerozen 1968-; MM; P.E.S; Marc X; Bolus, Andy; Weyland, Jocko 1967-; Bastille 1929-1990; Lépine, Adeline; et al. (BATT Coop, 2018)
More than 50 small publications designed and produced during a 3 weeks workshop hosted by BATT. Stéphane Prigent was leading the effort. With contributions from Hotu, PES, Hendrik Hegray, Andy Bolus, Marc X and myself. Benefits from the sales will fund the production of the next NK issue. (https://ceramicdwelling.tumblr.com)
Offsetdruck(?) - Umschlag: farbig. - Auflage 30 Exemplare
Katalog von Publikationen und Druckgrafiken, die während eines dreiwöchigen Workshops, der von BATT Coop veranstaltet wurde, entworfen und produziert wurden
Keywords: Graphzine